2013
DOI: 10.46298/dmtcs.2356
|View full text |Cite
|
Sign up to set email alerts
|

Homomesy in products of two chains

Abstract: International audience Many cyclic actions $τ$ on a finite set $\mathcal{S}$ ; of combinatorial objects, along with a natural statistic $f$ on $\mathcal{S}$, exhibit ``homomesy'': the average of $f$ over each $τ$-orbit in $\mathcal{S} $ is the same as the average of $f$ over the whole set $\mathcal{S} $. This phenomenon was first noticed by Panyushev in 2007 in the context of antichains in root posets; Armstrong, Stump, and Thomas proved Panyushev's conjecture in 2011. We describe a theoretical frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 0 publications
2
59
0
Order By: Relevance
“…More precisely, if ϕ is an invertible operator acting on a combinatorial set X, and f : X → R is some statistic on X, then we say that f is homomesic with respect to the action of ϕ on X if the average of f along every ϕ-orbit is equal to the same constant. The study of homomesies for combinatorial operators was initiated by Propp and Roby [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely, if ϕ is an invertible operator acting on a combinatorial set X, and f : X → R is some statistic on X, then we say that f is homomesic with respect to the action of ϕ on X if the average of f along every ϕ-orbit is equal to the same constant. The study of homomesies for combinatorial operators was initiated by Propp and Roby [29].…”
Section: Introductionmentioning
confidence: 99%
“…The systematic investigation of homomesies was initiated by Propp and Roby [29]. There has been a particular emphasis on exhibiting homomesies for rowmotion, including its piecewise-linear and birational extensions [25,1,29,13,32,10,22,15,19,23].…”
mentioning
confidence: 99%
“…Indeed, the past 10 or so years has seen the emergence of the subfield of Dynamical Algebraic Combinatorics [22,24], in which rowmotion features prominently. Furthermore, Panyushev's "constant average cardinality along orbits" observation was one of the first instances of homomesy [20], a phenomenon that again is at the heart of Dynamical Algebraic Combinatorics.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Rotation of binary words, and parabolic cosets of Weyl groups. Under the "Stanley-Thomas word" bijection (see [65,54]), rowmotion of J (R(a, b)) corresponds to rotation of binary words with a 1's and b 0's. Extending this description, Rush and Shi [60] showed that if P is the minuscule poset corresponding to the minuscule weight λ, then under the natural isomorphism J (P ) ≃ W/W J , where W J is the parabolic subgroup of the Weyl group W stabilizing λ, the action of rowmotion is conjugate to the action of a Coxeter element c ∈ W .…”
Section: Rotation Of Noncrossing Matchings and Webs A Noncrossing Mat...mentioning
confidence: 99%